International rent sharing and takeovers. Issue 2 (3rd May 2016) - Konings, Jozef; Marcolin, Luca; van Beveren, Ilke
Abstract : Purpose: – The purpose of this paper is to provide empirical evidence of international rent sharing in multinational enterprises. It looks at changes in rent sharing before and after the acquisition of a company by a foreign entity, and assesses the role of target and acquirer profitability in the wage setting process for the target firm. It therefore contributes to the evaluation of the impact of a form of globalization (inward foreign direct investment (FDI)) onto wages. Design/methodology/approach: – The authors use a unique firm level longitudinal dataset of M & As in Belgium between 1998 and 2010. The authors construct a micro-level dataset containing takeover and accounting information for target and acquiring firms. The empirical set up permits to net the estimates from selection effects in the choice of target firm, using propensity score matching and a difference-in-difference approach. Findings: – The authors find evidence that the deal does not significantly affect the degree of domestic rent sharing, but it enables international rent sharing. The authors qualify the results in terms of the acquirer's location, industry link with the target and controlling stake. Further robustness specifications include different profits and controls, and a comparison with a sample of domestic acquisitions. Research limitations/implications: – The sample of matches for acquired firms is constructed using propensity scores, which may not perfectly capture the differences between targeted and non-targeted companies. Although estimates should be net of selection effects, other sources of endogeneity may still make the estimates inconsistent. Practical implications: – Updating the discussion on the labor market consequences of globalization, and on foreign takeovers in particular. Social implications: – The discussion on international takeover should take into account not only the extensive margin (i.e. labor adjustments) but also salaries. The authors argue that through a precise channel (rent sharing) international takeovers of domestic companies may benefit the domestic labor force. Originality/value: – The dataset was constructed for the purposes of this analysis; rent sharing is tested in a takeover scenario for the first time, thus avoiding selection biases.